Simultaneous Determination of Seven Inorganic Anions in 18 Wines Samples by Suppressed Ion Chromatography - Dilek Bilgic Alkaya (Science Faculty of Chiang Mai University, 2019)
An ion chromatographic (IC) method with suppressed conductivity detection (CD) was developed and validated for the quantitative determination of fluoride, chloride, nitrite, nitrate, sulphite, sulphate, phosphate ions in 18 wine samples (W: white wine samples; R: red wine samples). A mixed solution of sodium carbonate and sodium hydroxide was used as the mobile phase. Simultaneous determination of seven inorganic anions (i.e. fluoride, chloride, nitrite, nitrate, sulphite, sulphate, phosphate) was completed in approximately 22 min. Effect of sodium carbonate and sodium hydroxide concentrations in the mobile phase, effect of flow rate of mobile phase were examined. Limit of quantification was found 0.50 mg.L-1.